Izzivi obveznega zdravstvenega zavarovanja - Strban, Grega (Delavci in delodajalci, 2014)
Mandatory health insurance in Slovenia is already for some time facing challenges. It should be adjusted to ever changing relations in the society. The present paper tackles the challenges related to finding the appropriate balance between public and private responsibility for health, in Slovenia and within the EU. Typology and purpose of cost sharing arrangements for health care is being analysed and some alternatives proposed. Questions of delimiting between public and private responsibility emerge also with payment of the sickness cash benefit, which may be claimed from the employer or from mandatory health insurance carrier. Especially in the EU the very tense relation between social rights and internal market (economic) freedoms when claiming health care in another member state is presented. It is emphasised that this is even more the case after adoption of the Directive 2011/24/EU and the recent decision of the Slovenian Constitutional Court.
Keywords: obvezno zdravstveno zavarovanje; odgovornost; zaposleni; zdravje; zdravstveno zavarovanje